Caught in the ESKAPE: Wildlife as Key Players in the Ecology of Resistant Pathogens in a One Health Context - Vanessa Silva; Sara Araújo; Manuela Caniça; José Eduardo Pereira; Gilberto Igrejas; Patrícia Poeta (Diversity)
The emergence of antimicrobial-resistant bacteria poses a significant global health challenge, with ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter spp.) playing a major role in multidrug-resistant infections. While traditionally associated with hospital settings, these bacteria have increasingly been detected in wildlife, suggesting a complex web of transmission between human, animal, and environmental reservoirs. Wildlife may act as both sentinels and reservoirs for resistant pathogens, contributing to their persistence and dissemination across ecosystems. This review explores the presence of ESKAPE bacteria in wild animals, examining their clonal lineages, resistance profiles, and virulence traits. Understanding how these pathogens circulate in natural environments is crucial for designing effective strategies to mitigate antimicrobial resistance. By adopting a One Health perspective—integrating human, animal, and environmental health—efforts to control ESKAPE bacteria can extend beyond clinical interventions to broader ecological and public health frameworks. Addressing this issue requires comprehensive surveillance, responsible antibiotic use, and policies aimed at reducing environmental contamination, ultimately safeguarding both biodiversity and global health.